Anxiety, Distress, and the Visual Process. - Brown, Evan; Optom, B. (Optometry & Visual Performance, 2019)
Anxiety, sympathetic nervous system arousal, stress, and distress are frequently encountered states of behavioural disposition in symptomatic patients presenting for visual assessment. Our unique percept of safety and threat is an individual response that lies within a continuum from mild to severe, dependent upon the helixing of multiple genetic, environmental, and psychological factors. Each individual response, the embeddedness of the response, and the frequency and length of the stimulus influence the chemical cascade affecting our central and autonomic nervous systems and the functioning of our sensory-motor process. This impacts our ability to derive meaning and direct action. This paper reviews the effects that distress and anxiety have on the visual process and the diagnostic signs that might alert a behavioural optometrist. It also proposes considerations for the treatment of visual conditions associated with or caused by sympathetic nervous system arousal.